2020
DOI: 10.1108/jmlc-07-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Detecting money laundering transactions with machine learning

Abstract: Purpose The purpose of this paper is to develop, describe and validate a machine learning model for prioritising which financial transactions should be manually investigated for potential money laundering. The model is applied to a large data set from Norway’s largest bank, DNB. Design/methodology/approach A supervised machine learning model is trained by using three types of historic data: “normal” legal transactions; those flagged as suspicious by the bank’s internal alert system; and potential money laund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 22 publications
3
76
0
3
Order By: Relevance
“…Research published [19,22,39,49,57] in subsequent years reported that tree-based classifiers can effectively detect money laundering activities, e.g., Savage et al [39] reported that RF in conjunction with network analysis and community detection can effectively classify whether transactions were associated with money laundering. Jullum et al [22] employed XGBoost when detecting money laundering at a transaction level, due to its: (i) efficiency, (ii) scalability, and (iii) ability to reduce training time by utilising the GPU, and they noted that it outperformed a rule-based system with manual inspection (a common approach used in banks). Both RF and XGBoost are Decision Tree (DT) ensembles; however, the latter is a boosting algorithm, while RF is a bagging approach.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Research published [19,22,39,49,57] in subsequent years reported that tree-based classifiers can effectively detect money laundering activities, e.g., Savage et al [39] reported that RF in conjunction with network analysis and community detection can effectively classify whether transactions were associated with money laundering. Jullum et al [22] employed XGBoost when detecting money laundering at a transaction level, due to its: (i) efficiency, (ii) scalability, and (iii) ability to reduce training time by utilising the GPU, and they noted that it outperformed a rule-based system with manual inspection (a common approach used in banks). Both RF and XGBoost are Decision Tree (DT) ensembles; however, the latter is a boosting algorithm, while RF is a bagging approach.…”
Section: Related Workmentioning
confidence: 99%
“…These models were implemented using xgboost, 1 lightgbm, 2 and catboost. 3 Hyperparameter optimisation was applied, as gradient boosting algorithms have a significant amount of parameters, and so, tweaking these parameters could improve results [15,22,37,52]. We opted to make use of Bayesian hyperparameter optimisation, more specifically, Tree Structured Parzen Estimator (TPE) [5], since it showed its effectiveness in highdimensional search spaces [37,52], when compared to other approaches [52].…”
Section: Offline Gradient Boosting Classifiersmentioning
confidence: 99%
See 2 more Smart Citations
“…Another intelligence, the infrared image based analysis, can also be implemented and used to predict the harvest time. Same as in machine learning in the money laundering [8].…”
Section: Agriculturementioning
confidence: 99%